Philosophical studies - "Moore, G..E" (London, 1960)
In this lucid and accessible book,G E Moore explores the central questions of philosophy thoughtfully, clearly, and with humour. He demonstrates that philosophy is an indispensable key to understanding our lives, and far from being an arcane academic discipline, can be enjoyed by all.
Keywords: Philosophy